EFEKTIFITAS IMPLEMENTASI PENGELOLAAN DANA DESA BERDASARKAN PERMENDAGRI NOMOR 20 TAHUN 2018 TENTANG PENGELOLAAN KEUANGAN DESA DI DESA TATENGESAN - Steven Tarore; Mary Vanye Sandag (JOURNAL AKSES STIA MALANG, 2022)
In terms of village finances, the village government is required to prepare a Report on theRealization of the Implementation of the Village APB and an Accountability Report on the Realizationof the Implementation of the Village APB. This report is generated from a village financial managementcycle, starting from the planning and budgeting stages; implementation and administration, toreporting and accountability for village financial management. This research uses qualitative research,primary data is collected through interview techniques, and is supported by secondary data, namelydocumentation. Analysis of the research data uses an interactive model consisting of "data collection,data display, data condensation, conclusing; drawing and verifying” developed by Miles, Hubermanand Saldana.The results of this study prove that the Village Fund Allocation (ADD) can be resolved properly.Accountability Add management in increasing physical development is still not effective, because thereis also no evaluation of activities that should be carried out with the people of Tatengesan Village. The capacity of human resources is still inadequate, as evidenced by their inability to optimally manageADD activities. Community participation in the management of ADD is still relatively low, as evidencedby the almost no involvement of the community at each stage of ADD management. The VillageGovernment must really understand the duties and responsibilities, especially in the management ofADD and the role of the BPD as a reservoir of community aspirations also needs to be improved.Keywords: Policy Implementation, Planning, Implementation, Accountability, Village Funds